Policy Strategy for Licensing Reform and Strengthening Monitoring Technology to Break the Cycle of Karhutla Haze in Indonesia - Frisca Ayu Suciandika (STMIK Indonesia Banda Aceh, 2026)
Indonesia has the world's third-largest tropical forest area (125.9 million hectares) but faces serious threats from forest and land fires (Karhutla). This research aims to identify the root causes of Karhutla and formulate strategic policies to address them. The analytical methods used include APKL (Actual, Problematic, Public Interest, Feasible) and USG (Urgency, Seriousness, Growth) to prioritize problems, and the Bardach method to evaluate policy alternatives. Data shows a 9.43% increase in hotspots from 1,601 points (2024) to 1,752 points (2025), acute respiratory infections increased from 380,000 to 420,000 cases, and economic losses reached IDR 95 trillion. Analysis results identify weak law enforcement as the priority issue (APKL score: 20), with the main root cause being overlapping regulations and licensing (USG score: 15). The recommended policy is sectoral regulatory harmonization through Presidential Regulation involving the formation of a Harmonization Team, preparation of an integrated Academic Paper, and implementation of One Map Policy. The novelty of this research lies in its comprehensive approach integrating multi-criteria analysis to produce evidence-based policy recommendations that can address the root causes of Karhutla fundamentally and sustainably.